1985
DOI: 10.2331/suisan.51.1175
|View full text |Cite
|
Sign up to set email alerts
|

Tetrodotoxin as a biological defense agent for puffers.

Abstract: The skin of toxic puffers (Fugu niphobles, F. vermicularis vermicularis and F. pardalis) was found to release 5-80MU of tetrodotoxin (TTX) per specimen when lightly stimulated by handling. The puffer did not release any more toxin when the handling stimuli were repeated 3-5 times at a 30 min-interval. Some of them, however, recovered to release TTX on handling stimulus when kept intact for two weeks. The cultured puffer (F. rubripes rubripes) specimens which were arti ficially toxified by feeding with toxic pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…A similar result was obtained in oral administration experiments (Kono et al, 2008), suggesting that, under natural conditions as well, pufferfish take up most of the ingested TTX into the liver first. During the ordinary period, some of the TTX taken up into the liver is gradually transferred to the skin, where it accumulates in the basal cells and/or TTX-bearing secretory glands or cells (succiform cells) of the epithelia (Kodama et al, 1986, Tanu et al, 2002, Mahmud et al, 2003a, 2003b, and is excreted by external stimuli under certain circumstances (Kodama et al, 1985, Saito et al, 1985. During the maturation period, the toxin transfer to the skin decreases somewhat, and most of the TTX taken up into the liver would be transported to the ovary, presumably with the precursors of yolk proteins that are synthesized in the liver (Wallace, 1985, Specker andSullivan, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was obtained in oral administration experiments (Kono et al, 2008), suggesting that, under natural conditions as well, pufferfish take up most of the ingested TTX into the liver first. During the ordinary period, some of the TTX taken up into the liver is gradually transferred to the skin, where it accumulates in the basal cells and/or TTX-bearing secretory glands or cells (succiform cells) of the epithelia (Kodama et al, 1986, Tanu et al, 2002, Mahmud et al, 2003a, 2003b, and is excreted by external stimuli under certain circumstances (Kodama et al, 1985, Saito et al, 1985. During the maturation period, the toxin transfer to the skin decreases somewhat, and most of the TTX taken up into the liver would be transported to the ovary, presumably with the precursors of yolk proteins that are synthesized in the liver (Wallace, 1985, Specker andSullivan, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural studies demonstrated that some fish species reject toxic puffer tissues and artificial food pellets containing tetrodotoxin (Yamamori et al . 1980, cited in Saito et al . 1984; Yamamori et al .…”
Section: Natural Deterrentsmentioning
confidence: 99%
“…In other cases, fish release secretions that are clearly toxic or deterrent, as in the secretions of boxfish (Ostracion lentiginosus, Ostraciidae; Thomson, 1964), puffers (Tetraodontidae; Saito et aL, 1985), soapfishes (Grammistidae; Randall et al, 1971), soles (Pardachirus pavoninus and P. marmoratus, Soleidae; Clark and George, 1979;Tachibana, 1984), and marine catfish (Arius thallasinus; AI-Hassan etaL, 1987). However, these secretions may serve as alarm pheromones to conspecifics, as well as being predator deterrents.…”
Section: O T H E R P O T E N T I a L A L A R M P H E R O M O N E S Inmentioning
confidence: 99%